2006
DOI: 10.1021/la0534367
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Mechanistic Investigation of a Phosphate-Modified HZSM-5 Catalyst for Methanol Conversion

Abstract: Phosphorus modification of a HZSM-5 (MFI) zeolite by wet impregnation has long been known to decrease aromatic formation in methanol conversion chemistry. We prepared and studied a catalyst modified by introducing trimethylphosphine under reaction conditions followed by oxidation. Magic-angle spinning (MAS) NMR shows that extensive dealumination occurs, resulting in a catalyst with a much higher framework SiO2/Al2O3 ratio, as well as extraframework aluminum and approximately 1.4 equiv of entrained phosphoric a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
74
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(79 citation statements)
references
References 27 publications
5
74
0
Order By: Relevance
“…12a. 9 The appearance of the broad band in FT-IR between 3520 cm À1 and 3200 cm À1 , which indicates intramolecular bonds between framework protons and oxygen, supports this. 40 Furthermore, OFAl species that can coordinate with three water molecules, appear to be able to coordinate with phosphorus as well.…”
Section: Reversible Phosphorus-framework Interactionsmentioning
confidence: 71%
See 3 more Smart Citations
“…12a. 9 The appearance of the broad band in FT-IR between 3520 cm À1 and 3200 cm À1 , which indicates intramolecular bonds between framework protons and oxygen, supports this. 40 Furthermore, OFAl species that can coordinate with three water molecules, appear to be able to coordinate with phosphorus as well.…”
Section: Reversible Phosphorus-framework Interactionsmentioning
confidence: 71%
“…29 Haw and co-workers suggested that phosphorus interacts with framework aluminium through hydrogen bonds. 9 This was supported by an early paper of Lischke et al in which the reversible character of the phosphorus framework interaction was described, as phosphorus could be eluted using a hot water washing step. After a hydrothermal treatment phosphorus could not be washed out, which was attributed to the formation of insoluble extra-framework AlPO 4 species.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…High selectivity of propylene has been obtained on modified ZSM-5 zeolites [2,3]. Phosphorusmodified ZSM-5 has been extensively investigated in methanol conversion [4][5][6][7][8][9][10][11][12][13][14], and catalytic cracking reaction [15][16][17][18][19][20]. The structure of p-modified ZSM-5 has been characterized by many research groups [21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%